An electronic aromaticity index for large rings. Issue 17 (15th February 2016) - Matito, Eduard
Abstract : We introduce a new electronic aromaticity index, AV1245, consisting of an average of the 4-center indices along the ring that keep a positional relationship of 1, 2, 4, 5. Abstract : We introduce a new electronic aromaticity index, AV1245, consisting of an average of the 4-center multicenter indices (MCI) along the ring that keeps a positional relationship of 1, 2, 4, 5. AV1245 measures the extent of transferability of the delocalized electrons between bonds 1–2 and 4–5, which is expected to be large in conjugated circuits and, therefore, in aromatic molecules. A new algorithm for the calculation of MCI for large rings is also introduced and used to produce the data for the calibration of the new aromaticity index. AV1245 does not rely on reference values, does not suffer from large numerical precision errors, and it does not present any limitation on the nature of atoms, the molecular geometry or the level of calculation. It is a size-extensive measure with low computational cost that grows linearly with the number of ring members. Therefore, it is especially suitable to study the aromaticity of large molecular rings such as those occurring in belt-shaped Möbius structures or porphyrins. The analysis of AV1245 in free-base and bis-metalated Pd [32]octaphyrins(1, 0, 1, 0, 1, 0, 1, 0) completes this study.